The community profiles of symbiotic bacteria at the different life stages of coral Dipsastraea favus - Xu, Jianjun; Chai, Guangjun; Xiao, Yilin; Xie, Ziqiang; Yang, Xiaodong; Liao, Baolin; Xiao, Baohua; Li, Zhiyong (Frontiers in Marine Science, 2023)
Corals live in a symbiotic relationship with various bacteria that are fundamental to host fitness, health, and survival. Though the diversity of symbiotic bacteria has been revealed in the early life stages of some corals, the dynamic bacterial community profiles of one coral are still poorly characterized, particularly the stage-specific bacteria. In this study, the bacterial communities in the patent, eggs, and 4-day-old planula larvae of a hermaphrodite coral Dipsastraea favus were investigated by high-throughput sequencing of 16S ribosomal RNA gene. As a result, dynamic profiles of bacterial community in the parent, eggs and larvae of D. favus were suggested. The bacterial diversity in the planula larvae was a bit higher than that in the D. favus parent, and distinct stage-specific symbiotic bacteria were detected, e.g., Oceanospirillaceae, Kordia, and Legionellaceae in D. favus larvae, and Kiloniellales and Prosthecochloris in adult D. favus. The dynamic change of bacterial community in coral adults and larvae may expand our understanding of the complex relationship between coral host and its symbiotic microbiota.